The Jewish Middle Ages - Bakhos, Carol; Langer, Gerhard, 1960- (Atlanta : SBL Press, 2023)
"For many, the Middle Ages in general evokes a sense of the sinister and brings to mind a world of fear, superstition, and religious fanaticism. For Jews it was a period marked by persecutions, pogroms, and expulsions. Yet at the same time, the Middle Ages was also a time of lively cultural exchange and heightened creativity for Jews. In The Jewish Middle Ages, contributors explore the ways in which the stories of biblical women, including, Eve, Sarah, Hagar, Rebekah, Zipporah, Ruth, Esther, and Judith, make their way into the rich tapestry of medieval Jewish literature, mystical texts, and art, particularly in works emanating from Ashkenazic circles"--
Gender and daily life in the Jewish communities of medieval Europe / Elisheva Baumgarten -- "If you keep silent in this crisis" (Esth 4:14): Esther the medieval biblical heroine / Constanza Cordoni -- Judith in the Hebrew literature of the Middle Ages / Dagmar Börner-Klein -- The tradition of Eve in the commentaries of Rashi and Ramban / Gerhard Langer -- Sarah and Hagar in medieval Jewish commentaries / Carol Bakhos -- The voice of the woman: narrating the Song of Songs in twelfth-century rabinnic exegesis / Robert A. Harris -- The irony of the Eshet Hayil: Proverbs 31:10-31 in Jewish medieval exegesis / Sheila Tuller Keiter -- Representations of biblical women in the writings of the Hasidei Ashkenaz / Judith R. Baskin -- Biblical women in the Hebrew poetry of Al-Andalus / Aurora Salvatierra Ossorio -- The female figure Zion in the liturgical literature of Al-Andalus / Meret Gutmann-Grün -- The development of the feminine dimension of God in the Jewish mystical tradition / Rachel Elior -- The biblical woman who is not in the Bible: feminine imagery in Kabbalah / Felicia Waldman -- The figure of Ruth as a convert in the Zohar / Yuval Katz-Wilfing -- Female protagonists in medieval Jewish book art / Katrin Kogman-Appel.
Includes bibliographical references and idexes
Carol Bakhos is Professor of Near Eastern Languages and Cultures and of Study of Religion at the University of California, Los Angeles (UCLA). Gerhard Langer is a professor at the Institute for Jewish Studies at the University of Vienna.
Print version record.
eBooks on EBSCOhost
Keywords: Bible. -- Criticism, interpretation, etc., Jewish -- History -- To 1500.; Bible -- Influence -- Medieval civilization; Bible -- Influence -- Civilisation médiévale.; Women in the Bible; Women in Judaism -- Europe -- History -- To 1500.; Judaism -- Europe -- History -- To 1500.; Jews -- History -- 70-1789.; Middle Ages; Juifs -- Histoire -- 70-1789.; Moyen Âge.; Femmes dans la Bible; Judaïsme -- Europe -- Histoire -- Jusqu'à 1500.